USING OF MSC WITH DIFFERENT ONTOGENETIC MATURITY FOR CORRECTION OF CHRONIC FIBROSING LIVER DAMAGE - M. Y. Shagidulin; A. A. Gorkun; N. A. Onishchenko; M. E. Krasheninnikov; I. M. Iljinsky; N. P. Mogeiko; L. V. Bashkina; I. N. Saburina; V. I. Sevastjanov; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Aim. To compare the effectiveness of MSC with different degree of ontogenetic maturity (MSC bone marrow – MSC BM and MSC umbilical cord – MSC UC) on regenerative processes in injured liver. Methods. In 4 groups of experiments on Wistar rats (n = 80) with a model of fibrotic toxic liver damage (FLD) it was studied the effect of MSCs with different degree of ontogenetic maturity on recovery processes at the regeneration of damaged liver: 1 gr. – Control, 2 gr. and 3 gr. introduction of MSC BM, included in Sphero®GEL-long in doses of 2.5 ×106 and 5.0 x 106 cells, respectively, and 4 gr. – introduction of MSC UC in the form of cell-spheroids (8–10 × 105 cells). The cells were injected into the damaged liver in 7 days after the end of FDL-modeling. The effect of cell therapy was studied during 180 days. The effectiveness of corrective therapy was evaluated by the results of functional and morphological investigations of livers (histological control of parenchymal and nonparenchy- mal liver tissue). Results. MSC BM in both doses and MSC UC contributed to a more rapid normalization of liver enzyme indices compared with the control (1 gr.), but the differences in the rate of recovery of disturbed enzymatic liver functions between groups 2, 3 and 4 – were absent. In 90 days after the cell application it was determined a more pronounced recovery activity of cells in groups 3 and 4; in 180 days the more pronounced activation of recovery processes was observed in group 3; but in group 4 the sclerotic processes were more pro- nounced in this period. Conclusion. For the induction of recovery processes in damage liver it is advisable not to use the MSC UC, but to use MSC BM in the Sphero®GEL, because MSC BM exert not only local but also systemic immune-regulatory effect, increasing the pool of T-reg. cells, which are additional carriers of regenera- tion information in organism.